User-comfort oriented optimal bidding strategy of an electric vehicle aggregator in day-ahead and reserve markets - Sengor, Ibrahim; Cicek, Alper; Erenoglu, Ayse Kubra; Erdinc, Ozan; Catalao, Joao P. S. (ELSEVIER SCI LTD, 2020)
With the increase in the number of electric vehicles (EVs), there might be substantial problems due to the charging transactions in the power system and the balancing between supply and demand sides can be provided in the modern power system by considering EVs as a flexible load. EVs cannot directly participate in buying and selling energy from/to the electricity market because of their relatively low energy and power capacities. In this manner, considering that EVs are generally parked during the day, an EV parking lot (EVPL) can offer economic charging opportunities to EV owners as multiple EVPLs can offer/bid for the buying/selling from/to the electricity market through an EVPL aggregator (EVPLA). In this study, a model in which the EVPLA offers/bids for the day-ahead (DA) and secondary reserve market in order to minimize the total cost is propounded. Furthermore, uncertainties related to the EV owners' behavior and market prices are handled by considering scenarios with real data in a stochastic manner. In addition, the EVPLA also takes into account the comfort of the EV owners when carrying out this operation. The comfort of EV owners as an essential issue similar to serving EV owners more economically is achieved by sustaining the minimum desired charge level by EV owners at the departure time. The results consist of a set of case studies to reveal the effectiveness of the proposed model considering the pricing conditions in Turkey, Finland, and USA-PJM DA and reserve markets. According to the results of the study, it is observed that an EV aggregator participating in DA and RE markets can make a significant profit for the three market conditions. An important result is also that the profit by the participation in reserve markets increases significantly compared to solely DA market participation.
Keywords: Electric vehicle; Electric vehicle aggregator; Electric vehicle parking lot; Electricity market; Optimal bidding; MANAGEMENT; ENERGY; Engineering